(untitled) (Journal of Teaching and Research in English Literature, 2017)
Way back in the forties of the last century, Rene Wellek raised a pertinent question which has set the minds of literary historians thinking: “Is it possible to write literary history, that is, to write that which will be both literary and a history.” The present article proposes some directions in which such an attempt could go. Let us realise that literary histories get written again and again; there cannot be just one literary history of a nation or a period. The extreme view would be that we need no literary history since its objects are always present, echoing Eliot’s well-known dictum that the whole of literature of Europe from Homer has a simultaneous existence and composes a simultaneous order. They are eternal and so do not have a history in the usual sense. Such a view ignores the simple concept of literary evolution in arts though it may sound abstract. The real problem is how to provide a framework for such a literary history.